Potassium Titanate Assembled Titanium Dioxide Nanotube Arrays Endow Titanium Implants Excellent Osseointegration Performance and Nerve Formation Potential - Zhao, Hang; Liu, Feng; Yin, Yixin; Wang, Shuhua (Frontiers in Chemistry, 2022)
For titanium-based material bone repair, most researchers have focused on osseointegration at the implant–bone interface; however, neuralization is always ignored, despite the importance of the nervous system for functional rebuilding during bone repair. Herein, we propose a functional surface modification approach by constructing a potassium titanate nanorod-decorated titanium oxide nanotube array on the surface of a titanium implant using an electrochemical technique following a hydrothermal approach. The K2Ti6O13-TiO2 hybrid nanotube array on titanium implants possesses multifunctional performance to both enhance the osteogenic differentiation of mesenchymal stem cells and neural differentiation of neural stem cells due to the release of potassium ions from the K2Ti6O13-TiO2 hybrid nanotubes. The enhancement of the osteogenic differentiation of mesenchymal stem cells is derived from the special nanostructures of titanium oxide nanorods, and the release of potassium ions from layer-structured potassium titanate accelerates the neural differentiation of neural stem cells. This strategy of designing and preparing multifunctional hybrid implantable bone repair materials provides a new approach to the formation of different tissues on the surface of implants, which will have great applications in the formation of a fully functional interface in bone repair.